As paixões aristotélicas nas canções de Zé Mira: o caipira do Vale do Paraíba do Sul - Silva, Fabíola Mirella Dias Roque da (2021)
The present work is a rhetorical study of the passions in the lyrics of two songs by the guitar player Zé Mira (José Alves de Mira – 24/10/1924 -23/08/2008) and seeks to establish the ethos of the hillbilly and the capacity he has to to arouse passions (pathos) in the audience through the discussion of themes of common interest in the lyrics of the songs. The research is based on the theories of passions of Aristotle (2011), on the conceptions of the new Rhetoric of Perelman and Olbrechts-Tyteca (2014), of scholars such as Amossy (2005), Meyer (2004). Reboul (2004) and Ferreira (2010) and considers the lyrics of the caipira song as an argumentative text that prints in the auditorium a way of existing, of seeing the world from a very specific perspective that, in our days of predominance of urban themes in Brazilian songs, it needs to fulfill three pillars of classical rhetoric: docere (teach), movere (move) and deletere (please). The general objective of our research was to analyze how the speaker made use of the Aristotelian passions in the works of Zé Mira and how they were configured in the two lyrics of chosen songs that portrayed problems common to life in society (political and social). From this initial conception, the specific objectives were outlined: recognizing political and social issues in the songs (from concerns regarding ecological issues to social issues involved with national politics), pointing out the rustic dialect and the studies of linguistic peculiarities contained in the songs, to expose the speaker's intentions to persuade the audience in favor of his theses through the pathetic effects in the songs to highlight the realization of the ethos and the argumentative aspects linked to the logos. We conclude that the speaker applied the epidictic genre and used the derivative of the value of the person – to explore the qualities and hierarchies, merits and dignity of the river, he used rhetorical figures to highlight his relationship with nature and resorted to the established discourse to rank a place of “power”. He applied docere and movere in favor of the river to teach that he needs to be saved and aroused feelings of fear, compassion, respect and awe